2016
DOI: 10.1007/s00424-016-1927-1
|View full text |Cite
|
Sign up to set email alerts
|

SO4 = uptake and catalase role in preconditioning after H2O2-induced oxidative stress in human erythrocytes

Abstract: Preconditioning (PC) is an adaptive response to a mild and transient oxidative stress, shown for the first time in myocardial cells and not described in erythrocytes so far. The possible adaptation of human erythrocytes to hydrogen peroxide (HO)-induced oxidative stress has been here verified by monitoring one of band 3 protein functions, i.e., Cl/HCO exchange, through rate constant for SO uptake measurement. With this aim, erythrocytes were exposed to a mild and transient oxidative stress (30 min to either 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 72 publications
1
50
1
Order By: Relevance
“…Band 3 protein is the most abundant integral membrane protein of erythrocytes [12,13], responsible for Cl -/HCO 3 exchange, which correlates with ion balance across membrane, osmotic properties, cell shape maintaining, gas exchange and, in turn, oxygenation of the entire organism [14]. These functions are mediated by both membrane and cytoplasmic domains via phosphorylation pathways, as recently shown [15,16]. Other studies have demonstrated a reversible interaction of Band 3 protein with hemoglobin and spectrin [17,18], suggesting that the efficiency of Band 3 protein reflects whole erythrocyte homeostasis.…”
Section: Introductionmentioning
confidence: 93%
“…Band 3 protein is the most abundant integral membrane protein of erythrocytes [12,13], responsible for Cl -/HCO 3 exchange, which correlates with ion balance across membrane, osmotic properties, cell shape maintaining, gas exchange and, in turn, oxygenation of the entire organism [14]. These functions are mediated by both membrane and cytoplasmic domains via phosphorylation pathways, as recently shown [15,16]. Other studies have demonstrated a reversible interaction of Band 3 protein with hemoglobin and spectrin [17,18], suggesting that the efficiency of Band 3 protein reflects whole erythrocyte homeostasis.…”
Section: Introductionmentioning
confidence: 93%
“…As cell size recovery is involved in PC response in neuronal‐like differentiated SH‐SY5Y cells, the role of ion conductances during adaptation and their use for pharmacological targeting in stroke and brain trauma could be reasonably considered. As a matter of fact, the evidence that 10μM H 2 O 2 –induced PC impacts on membrane transport systems has been recently proven by Morabito and co‐authors, reporting about the role of Band 3 protein in human erythrocytes PC. Nonetheless, this feature does not fall in the scope of the present study and can be the subject of future investigations.…”
Section: Discussionmentioning
confidence: 95%
“…Unexpectedly, MnSOD levels remained unchanged after both damage and PC, suggesting this antioxidant enzyme may be involved neither in detrimental nor protective H 2 O 2 effect at experimental conditions used here. As a matter of fact, previous investigations tried to verify whether endogenous antioxidant enzymes are key component of PC pathways . An increase in MnSOD has been detected after hypoxic PC both in vivo and in vitro, while Ravati et al showed upregulation for MnSOD but not for Cu/Zn SOD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations